Randomized controlled trial of adjunctive zinc-containing vaginal hydrogel following fluconazole therapy for vulvovaginal candidiasis - Dávid Rátonyi; Barbara Kozma; Bence Kozma; Attila G. Sipos; Peter Takacs (BMC Women's Health, 2026)
Abstract Background Recurrent and persistent vulvovaginal candidiasis remain clinically challenging, and supportive strategies that improve post-treatment microbiological stability are needed. Zinc-containing vaginal hydrogel may influence local host–pathogen interactions, but clinical data on its adjunctive use after fluconazole are limited. Methods This single-center, two-arm, parallel-group randomized clinical trial compared standard oral fluconazole therapy alone with fluconazole followed by adjunctive zinc-containing vaginal hydrogel. Women with symptomatic acute vulvovaginal candidiasis were assessed at baseline, week 4, week 8, and week 12. The primary outcome was clinical cure, defined as Candida Severity Score < 3. Secondary outcomes included symptom severity, Vaginal Health Index, mycological cure, and interim antifungal treatment. A post-clearance recurrence cohort included participants with both clinical and mycological clearance at week 4. Results Fifty-four women were included in the modified intention-to-treat cohort: 22 controls and 32 hydrogel-treated participants. Clinical cure did not differ significantly between groups at week 4, week 8, or week 12. Longitudinal models showed no significant group-by-time interaction for clinical cure, Candida Severity Score, Vaginal Health Index, VSQ-21, or interim antifungal treatment. At week 12, mycological cure was numerically more frequent in the hydrogel group than in controls, without reaching statistical significance (65.6% vs. 40.9%; OR = 2.76, 95% CI 0.90–8.45; p = 0.097). In the exploratory post-clearance recurrence cohort, week-12 culture negativity was observed in 14/14 hydrogel-treated participants and 11/17 controls (100.0% vs. 64.7%; p = 0.021), corresponding to microbiological culture recurrence rates of 0.0% and 35.3%, respectively. Conclusion Adjunctive zinc-containing vaginal hydrogel following oral fluconazole was not associated with a significant improvement in acute clinical cure in the overall study population. The observed maintenance of fungal culture negativity among women with documented early clinical and mycological clearance should be interpreted as an exploratory microbiological signal rather than definitive evidence of clinical recurrence prevention. Larger placebo-controlled trials specifically designed and powered for recurrent vulvovaginal candidiasis and culture-confirmed recurrence are needed. The study protocol was approved by the Hungarian National Institutional Review Medical Research Council (approval No. 3282-7/2023/EUIG). All participants provided written informed consent before any study-related procedure. The trial was registered at ClinicalTrials.gov (NCT05895162; registration date: 15 May 2023).